2018
DOI: 10.1021/acsomega.8b01423
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Food-Safe Water-Resistant Paper Coatings Using a Melamine Primer and Polysiloxane Outer Layer

Abstract: Paper-based materials are highly desirable as packaging materials due to their numerous advantages that include low cost, renewability, and biodegradability. However, their hydrophilicity has limited their range of applications. Reported herein is a facile and economical approach for the preparation of biodegradable water-resistant paper for food-contact applications. Commercial printing paper and cup papers are coated with melamine, which is FDA approved for food-contact applications. Subsequently, a water-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 32 publications
2
48
0
Order By: Relevance
“…The IR spectra of this finished coating did not exhibit any NCO peaks at 2270 cm −1 , indicating a complete curing treatment (SCH-7). In addition, a peak appeared at 1260 cm −1 corresponding to the Si-CH 3 stretching vibration of the indicates the successful grafting of PDMS-NH 2 [40,49].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IR spectra of this finished coating did not exhibit any NCO peaks at 2270 cm −1 , indicating a complete curing treatment (SCH-7). In addition, a peak appeared at 1260 cm −1 corresponding to the Si-CH 3 stretching vibration of the indicates the successful grafting of PDMS-NH 2 [40,49].…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the harmful and persistent nature of fluorine-containing compounds in the environment, fluorine-free alternatives are highly desirable. In this regard, PDMS has recently been employed by our group and others to introduce self-cleaning properties [38,39,40,41,42,43,44,45]. In a recent study, polydopamine (PDA) coated fabric was treated with stearic acid to impart excellent water repellency.…”
Section: Introductionmentioning
confidence: 99%
“…The ATR-FTIR analysis, as shown in Figure 2, confirmed the grafting of PDMS in the PVOH/chitosan-g-PDMS coated paper by the presence of characteristic PDMS peaks at 1257.59 and 790.81 cm −1 which corresponds to Si CH 3 stretching and Si O Si bending vibrations in the PVOH/chitosan-g-PDMS coated paper. 11,28 Basis weight and thickness are important basic properties that highly influence the mechanical, barrier, and optical properties of the paper. 29 Therefore, selected samples were subjected to basis weight and thickness analysis as shown in Table 1.…”
Section: Repulpabilitymentioning
confidence: 99%
“…9 To address the above challenges, our group is actively working towards developing plastic-free, PFAS-free, costeffective water-and oil-resistant surfaces. [10][11][12][13][14][15] One of the key focus is the use of benign polydimethylsiloxane (PDMS) as an alternative to PFAS because PDMS is known for imparting water and oil repellent properties while still acceptable for food contact applications. [16][17][18][19][20][21][22] In a recent breakthrough study, we reported the fabrication of water-and grease-resistant coating using Chitosan-grafted-PDMS (Chitosan-g-PDMS), and the coated paper was 100% recyclable by washing the coating off.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides and proteins are biodegradable in nature and their use for paper coating is very appealing, but they are hydrophilic in nature and hence they have poor water resistance 10,19–21 . Recently, our group has developed chitosan‐ graft ‐silicone oil coatings for paper with good water and oil repellent properties 22–26 . Silicone oil was chosen because of its relatively food safe nature and exceptional water and oil repellent properties that have been demonstrated in various coatings 27–34 .…”
Section: Introductionmentioning
confidence: 99%